Pelanggaran Hak Asasi Manusia terhadap Warga Sipil di Palestina: Tinjauan Hukum Internasional dan Upaya Penyelesaian - Iklima Nur Sya`bani; Evita Putri; Nashrulloh Al Hasani; Queentoqo Haura; Budi Ardianto (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to identify the human rights (HR) violations experienced by Palestinian civilians in the context of international law and to evaluate the various conflict resolution efforts that have been undertaken. Based on an analysis of various forms of violations, such as killings, administrative detention without charges, movement restrictions, evictions, and disruptions to education and healthcare services, this research finds that HR violations against Palestinian civilians are widespread and systematic. The study also assesses the effectiveness of the resolution efforts made by the international community, such as the Oslo Accords and various UN resolutions. Although there have been some advancements, these efforts are often hindered by distrust, ongoing violence, and failures to address core issues. To achieve a fair and lasting resolution, this research recommends full respect for human rights, cessation of actions that violate international law, and a genuine commitment from all parties to meaningful negotiations. The type of research used is a library research method with descriptive analysis by collecting data, organizing or classifying it, compiling, and interpreting it. This method is used because it can clearly describe the object of the study.